Music Video's Performing Bodies: Floria Sigismondi as Gestural Animator and Puppeteer. (July 2015) - Perrott, Lisa
Auteur music video director Floria Sigismondi has a reputation for creating beautifully macabre imagery that has been described as surreal and uncanny. Less obvious is the way in which she uses animation and gesture to estrange the movement of performing bodies. While pixilation and stop motion animation are used together to invert the agency of humans and objects, Sigismondi's use of gesture extends this manipulation of agency beyond technical processes. This dialectic of cinematic agency is discussed through an examination of three music videos directed by Sigismondi: End of the World (2004) for The Cure, Montauk Fling (2013) for Lawrence Rothman and The Stars (Are Out Tonight) (2013) for David Bowie. Considering these videos in relation to puppet animation, live-action film and the cultural and historical migration of gesture, the author argues that Sigismondi puppetises humans and animates gesture as a means of transgression.